The Shifting Landscape of Prenatal Testing: Between Reproductive Autonomy and Public Health - Ravitsky, Vardit (The Hastings Center report, 2017)
Since the 1970s, prenatal testing has been integrated into many health care systems on the basis of two competing and largely irreconcilable rationales. The reproductive autonomy rationale focuses on nondirective counseling and consent as ways to ensure that women's decisions about testing and subsequent care are informed and free of undue pressures. It also represents an easily understandable and ethically convincing basis for widespread access to prenatal testing, since the value of autonomy is well established in Western bioethics and widely recognized by funders of health care. In contrast, the public health rationale approaches prenatal testing as designed to reduce the incidence of certain conditions in the population to reduce the burden of disease. This rationale emphasizes the societal consequences of reproduction and the aggregate impact of women's individual reproductive decisions on the overall health of future populations. In this essay, I argue that, despite what could be seen as a persistent failure to meet the ideals of reproductive autonomy, resisting the public health rationale as a basis for prenatal screening is ethically and pragmatically crucial. I recommend policy mechanisms that can enhance reproductive autonomy at a societal level to support choice at the individual level.